If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(k/3)+7=-20
We simplify the equation to the form, which is simple to understand
(k/3)+7=-20
Simplifying:
( + 0.333333333333k)+7=-20
Remove unnecessary parentheses
+ 0.333333333333k+7=-20
We move all terms containing k to the left and all other terms to the right.
+ 0.333333333333k=-20-7
We simplify left and right side of the equation.
+ 0.333333333333k=-27
We divide both sides of the equation by 0.333333333333 to get k.
k=-81
| 6*2-0.5b= | | a+4.9=4.1 | | 5x^2-21x-54=0 | | 3(y-1)=6(y+3) | | 4x/5-5x/2=2 | | -4(5+3x)=52 | | 9X^2=-6X+1 | | -7n-7n=-14 | | 13-b*4= | | -3(2n-8)=8(n+4)+6n | | -10+7p+10=18 | | -m/8=5/8 | | a^2(b-5)-25(b-5)=0 | | -5n^2-26n+40=0 | | n/2+2n/3=7 | | 2c-5=11 | | -34=v+42-5y | | 2x^2-2x=180 | | 7-(6a+11)=38 | | 4y=80 | | x^2+9x-3375=0 | | 5x+2.15=11 | | g-6=56 | | 2(m-4)=5m+7 | | -5n^2-26+40=0 | | 3(4-x)=x+2(x+3) | | 8x+2+5x+7=12x+4 | | 2x-6/4=2x | | 9x^2-2=3x | | 2x-6/4=2x-2 | | 98-4b=-11b-14 | | -3m=5(2-m) |